Intellectual Capital Dimensions and Financial Leverage of Indonesian Consumer Non-Cyclicals: The Mediating Role of Profitability - Fahriza Alfarisy; Zuwina Miraza; Hafriz Rifki Hafaz (Research Synergy Foundation, 2026)
This study aims to examine the mediating role of profitability in the relationship between intellectual capital and financial leverage. This study uses secondary data from consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2020–2023. Intellectual capital is measured through its dimensions, namely capital employed efficiency (CEE), human capital efficiency (HCE), structural capital efficiency (SCE), and relational capital efficiency (RCE). Profitability is proxied by Return on Assets (ROA), while financial leverage is measured using the debt-to-asset ratio (DAR) and debt-to-equity ratio (DER). Panel data regression and the Sobel test are employed to analyze the data. The results show that CEE, HCE, and SCE have a positive and significant effect on profitability, while RCE has no significant effect. When financial leverage is measured using DAR, only SCE has a significant effect, while CEE, HCE, RCE, and ROA are not significant. In contrast, when financial leverage is measured using DER, ROA has a significant negative effect, while CEE, HCE, SCE, and RCE are not significant. Furthermore, profitability mediates the relationship between intellectual capital dimensions (CEE, HCE, and SCE) and financial leverage when leverage is measured using DER, but not when leverage is measured using DAR. This study contributes to the literature by providing empirical evidence on the role of intellectual capital in shaping corporate financial decisions in Indonesia's consumer non-cyclical sector.